The Hegemony of Pesantren Ulama in the Contemporary Political Dynamics of Central Java - Yahya, Imam; Ananda, Muhammad Aflahmuna (JURNAL PENELITIAN, 2024)
This study aims to examine the hegemony of religious leaders (Ulama) in contemporary politics and how Ulama exercise their hegemonic roles in the political process in Central Java. Data was obtained through primary and secondary sources, with primary data collected through field research using interviews, and secondary data gathered through literature research. The findings indicate that the entanglement between Ulama and politics is caused by two factors: political oligarchy within political parties and the political hegemony of Ulama. The political hegemony of Ulama in the political constellation of Central Java makes them highly influential in political affairs. However, from the perspective of real political dimensions in Central Java, Ulama have yet to secure strategic positions in either the executive or legislative branches.